A recepção do iambo grego na sátira latina: Lucílio, Horácio, Pérsio e Juvenal - Cordeiro, Iana Lima (2023)
The Greek iambus, produced during Archaic Greece between VII and IV a.C. by Archillochus, Semonides and Hiponax, became known for its strong invective, i.e., for its attack on contemporary individuals or behaviors. We see this aspect also in imperial Roman satire, produced between II a.C. and II d.C., by Lucilius, Horace, Persius and Juvenal. The approximation between the two genres had already been established by the grammatician Diomedes, who defines both iambus and satire with the same expression: carmen maledicum. Thus, considering that, despite the temporal distance between them, there is Callimachus, during the Hellenistic period, writing iambos according to the hipponactean model and being imitated by Horace, we propose an approximation between archaic iambic and roman satiric invective. In order to demonstrate this ressemblance, we analyse thematic proximity from five categories: the constitution of the poetic persona, personal invective, invective towards women, attack on targets based on morality, and, at last, obscene language to describe sexual organs and intercourse.